Imaging Transcriptomics of Brain Functional Alterations in MS and Neuromyelitis Optica Spectrum Disorder - Li, Yuna; Sun, Jun; Zhuo, Zhizheng; Guo, Min; Duan, Yunyun; Xu, Xiaolu; Tian, Decai; Li, Kuncheng; Zhou, Fuqing; Li, Haiqing; Zhang, Ningnannan; Han, Xuemei; et al. (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: The underlying transcriptomic signatures driving brain functional alterations in MS and neuromyelitis optica spectrum disorder (NMOSD) are still unclear.MATERIALS AND METHODS: Regional fractional amplitude of low-frequency fluctuation (fALFF) values were obtained and compared among 209 patients with MS, 90 patients with antiaquaporin-4 antibody (AQP4)+ NMOSD, 49 with AQP4− NMOSD, and 228 healthy controls from a discovery cohort. We used partial least squares (PLS) regression to identify the gene transcriptomic signatures associated with disease-related fALFF alterations. The biologic process and cell type–specific signature of the identified PLS genes were explored by enrichment analysis. The correlation between PLS genes and clinical variables was explored. A prospective independent cohort was used to validate the brain fALFF alterations and the repeatability of identified genes.RESULTS: MS, AQP4+ NMOSD, and AQP4− NMOSD showed decreased fALFF in cognition-related regions and deep gray matter, while NMOSD (both AQP4+ and AQP4−) additionally demonstrated lower fALFF in the visual region. The overlapping PLS1− genes (indicating that the genes were overexpressed as regional fALFF decreased) were enriched in response to regulation of the immune response in all diseases, and the PLS1− genes were specifically enriched in the epigenetics profile in MS, membrane disruption and cell adhesion in AQP4+ NMOSD, and leukocyte activation in AQP4− NMOSD. For the cell type transcriptional signature, microglia and astrocytes accounted for the decreased fALFF. The fALFF-associated PLS1− genes directly correlated with Expanded Disability Status Scale of MS and disease duration across disorders.CONCLUSIONS: We revealed the functional activity alterations and their underlying shared and specific gene transcriptional signatures in MS, AQP4+ NMOSD, and AQP4− NMOSD.AHBAAllen Human Brain AtlasAQP4antiaquaporin-4 antibodyEDSSExpanded Disability Status ScalefALFFfractional amplitude of low-frequency fluctuationFDRfalse discovery rateGOgene ontologyHChealthy controlsKEGGKyoto Encyclopedia of Genes and GenomesNMOSDneuromyelitis optica spectrum disorderPASTAParamedic Acute Stroke Treatment AssessmentpFDRP value with false discovery rate correctedPLSpartial least squaresrsfMRIresting-state fMRI